Two Multiple Sclerosis Quality-of-Life Measures: Comparison in a National Sample. (14th January 2015) - Moore, Fraser; Vickrey, Barbara; Fortin, Kathy; Lee, Liesly
Abstract: Background : Multiple sclerosis (MS) has a profound impact on patients' health-related quality of life (HRQoL). It is unclear how HRQoL can be best assessed for different purposes. This study aimed to compare two HRQoL questionnaires of differing lengths for feasibility of administration, patient perceptions and psychometric properties. Methods : This was an open-label, 24-month study in 334 patients with relapsing MS treated with subcutaneous interferon β-1a. At baseline and months 6, 12, 18 and 24, patients completed the Multiple Sclerosis International Quality of Life (MusiQoL) and Multiple Sclerosis Quality of Life-54 (MSQOL-54) questionnaires and compared them using an evaluation questionnaire. HRQoL scores over time and psychometric properties (correlations with clinical disease measures, relative validity and responsiveness to change) of the questionnaires were assessed. Results : A minority of patients had missing items on either HRQoL measure. Completion time was significantly shorter for MusiQoL versus MSQOL-54 (p<0.0001). Patients felt that MusiQoL was easier to use than MSQOL-54 but preferred MSQOL-54 in terms of thoroughness. Mean HRQoL scores increased significantly from baseline to 24 months; correlations of both measures were stronger with an anxiety and depression measure than with disability or recent relapse occurrence. Relative validity and responsiveness to change were similar for both instruments. Conclusion : The shorter MusiQoL is suitable for evaluating HRQoL in patients with MS and may be more practical to administer than the more thorough MSQOL-54. RÉSUMÉ: Comparaison, dans un échantillon national, de deux mesures de la qualité de vie dans la sclérose en plaques : Contexte: La sclérose en plaques (SP) a un impact important sur la qualité de vie reliée à la santé (QVS) chez les patients qui en sont atteints. La meilleure façon d'évaluer la QVS à différentes fins demeure à préciser. Le but de l'étude était de comparer deux questionnaires de QVS de différente longueur pour évaluer la faisabilité d'administration, les perceptions des patients et les propriétés psychométriques. Méthode: Il s'agit d'une étude ouverte de 24 mois portant sur 334 patients atteints de SP cyclique traités par l'interféron ß-1a sous-cutané. Les patients ont complété les questionnaires Multiple Sclerosis International Quality of Life (MusiQoL) et Multiple Sclerosis Quality of Life-54 (MSQOL-54) au début de l'étude, à 6, 12, 18 et 24 mois du début et ils les ont comparés au moyen d'un questionnaire d'évaluation. Les scores au QVS et les propriétés psychométriques (corrélations avec les mesures de la maladie clinique, la validité relative et la capacité d'adaptation au changement) des questionnaires ont été évalués. Résultats: L'une ou l'autre des mesures de la QVS comportait des items manquants pour une minorité de patients. Le temps requis pour compléter les questionnaires était significativement plus court pour le MusiQoL que pour le MSQOL-54 (p<0, 0001). Les patients estimaient que le MusiQoL était plus facile à utiliser que le MSQOL-54, mais préféraient le MSQOL-54 qui est plus approfondi. Les scores moyens aux QVS avaient augmenté significativement à 24 mois par rapport aux scores initiaux. Les corrélations entre les deux mesures étaient plus fortes pour la mesure de l'anxiété et de la dépression que pour l'invalidité ou une récurrence récente de la maladie. La validité relative et l'adaptation au changement étaient semblables pour les deux instruments. Conclusion: Le Questionnaire MusiQoL, qui est plus court, est approprié pour évaluer la QVS chez les patients atteints de SP et peut être plus pratique à administrer que le MSQOL-54 qui est plus approfondi.